Accelerated Critical Therapy Now in the Emergency Department Using an Early Intervention Team: The Impact of Early Critical Care Consultation for ICU Boarders. (16th March 2022) - Jayaprakash, Namita; Pflaum-Carlson, Jacqueline; Gardner-Gray, Jayna; Hurst, Gina; Kinni, Harish; Tang, Amy; Coba, Victor; Rivers, Emanuel P.
Abstract : OBJECTIVES: Evaluate the impact of an emergency department (ED)–based critical care consultation service, hypothesizing early consultation results in shorter hospital length of stay (LOS). DESIGN: Retrospective observational study from February 2018 to 2020. SETTING: An urban academic quaternary referral center. PATIENTS: Adult patients greater than or equal to 18 years admitted to the ICU from the ED. Exclusion criteria included age less than 18 years, do not resuscitate/do not intubate documented prior to arrival, advanced directives outlining limitations of care, and inability to calculate baseline modified Sequential Organ Failure Assessment (mSOFA) score. INTERVENTIONS: ED-based critical care consultation by an early intervention team (EIT) initiated by the primary emergency medicine physician compared with usual practice. MEASUREMENTS: The primary outcome was hospital LOS, and secondary outcomes were hospital mortality, ICU LOS, ventilator-free days, and change in the mSOFA. MAIN RESULTS: A total 1, 764 patients met inclusion criteria, of which 492 (27.9%) were evaluated by EIT. Final analysis, excluding those without baseline mSOFA score, limited to 1, 699 patients, 476 in EIT consultation group, and 1, 223 in usual care group. Baseline mSOFA scores (±sd ) were higher in the EIT consultation group at 3.6 (±2.4) versus 2.6 (±2.0) in the usual care group. After propensity score matching, there was no difference in the primary outcome: EIT consultation group had a median (interquartile range [IQR]) LOS of 7.0 days (4.0–13.0 d) compared with the usual care group median (IQR) LOS of 7.0 days (4.0–13.0 d), p = 0.64. The median (IQR) boarding time was twice as long subjects in the EIT consultation group at 8.0 (5.0–15.0) compared with 4.0 (3.0–7.0) usual care, p < 0.001. CONCLUSIONS: An ED-based critical care consultation model did not impact hospital LOS. This model was used in the ED and the EIT cared for critically ill patients with higher severity of illness and longer ED boarding times.